A study on assessment of scholastic dropout and its determinants in adolescents residing in Raipur city of Chhattisgarh state - Minz, Anmol Madhur; Jain, Kamlesh; Soni, Gopal Prashad; Ekka, Abha (International Journal of Research in Medical Sciences, 2017)
Background: In India, adolescents (10-19 years) constitute one fifth of the total population providing promising pillar for our nation’s future. Being a sensitive and key transitional period of life adolescents living environment (Family, school, Peers etc.) can present new challenges for these adolescents and symptoms of dysfunction may occur. Schooling constitutes major part of adolescent’s life, moulding them for bright future but problem like scholastic dropout deprive them & can play as major factor determining their future perspective with regard to personal and social achievements. With this background, the present study was conducted to assess the prevalence of Scholastic dropout problems in adolescents, and its determinants in Raipur city (C.G.) India Methods: Cross-sectional community based study was done, using multi stage simple random sampling 32 study (urban & slum) areas was selected. 643 adolescents were interviewed with prior consent by house to house survey. Results: Problem of scholastic dropout was 10.89%. Major determinants contributing were socioeconomic status, mother’s education, family violence, poor academic performance, Substance abuse. Conclusions: Scholastic dropout seems to be small yet a prevalent problem in our society inspite of many government initiatives and as found in the study problem is multipronged indicating adoption of a holistic approach to alleviate whole environment in which adolescents live in.